Crystal structures and luminescence properties of a D–A type CIEgen and its Zn(ii) complexes. Issue 21 (14th May 2019) - Song, Jian-Biao; Liu, Gui-lei; Hao, Liang; Zhang, Fang; Li, Hui
Abstract : A D–A type CIEgen with a near-planar molecular structure and its two Zn(ii ) complexes with fluorescence selectivity for THF were obtained. Abstract : A D–A type organic luminogen single crystal (CIE-C ) and its two Zn(ii ) complexes [Zn(CIE-P)(C4 H4 N2 )·CH3 OH] (1 ) and [Zn(CIE-P)(4, 4′-bipy)·1.5CH3 OH] (2 ) (CIE-P = 2, 3-bis(2, 4-dihydroxybenzylideneamino)maleonitrile, C4 H4 N2 = pyrazine, 4, 4′-bipy = 4, 4′-bipyridine) have been synthesised and studied. The single crystal X-ray diffraction analysis showed that the molecular structure ofCIE-C is well planar and the good co-planarity is maintained in the 2D structure;1 and2 are all mononuclear complexes. The photoluminescence properties ofCIE-C and its Zn(ii ) complexes have been investigated in the solid state and solution. The novel crystallization-induced emission-enhancement (CIEE) behavior ofCIE-C and unusual fluorescence selectivity for THF of1 and2 were found.